2015
DOI: 10.21106/ijma.54
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Services Utilization in Yobe State, Nigeria: Examining Predictors and Barriers

Abstract: Objective:In Nigeria, wide disparities exist between the different parts of the country, with the states in the North East zone having poor health resources. The objective of this study is to assess whether women’s biological, sociocultural, and economic characteristics are associated with utilization of ante natal care services as measured by number of antenatal care (ANC) visits in Yobe State.Methods:This is a secondary data analysis of the 2008 Nigeria Demographic and Health Survey with records from 33,385 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…Engaging in skilled employement and small businesses as income sources among mother was associated with increased odds of utilizing recommended minimum number of ANC services which is consistent with those of previous studies in Ethiopia [21,24]. A study in Nigeria [44] reported that women who operated small businesses were 6 times more likely to make the recommended number of ANC clinics visits. Similar studies in Nepal and China also corroborate our findings [11,45].…”
Section: Discussionsupporting
confidence: 87%
“…Engaging in skilled employement and small businesses as income sources among mother was associated with increased odds of utilizing recommended minimum number of ANC services which is consistent with those of previous studies in Ethiopia [21,24]. A study in Nigeria [44] reported that women who operated small businesses were 6 times more likely to make the recommended number of ANC clinics visits. Similar studies in Nepal and China also corroborate our findings [11,45].…”
Section: Discussionsupporting
confidence: 87%
“…However, early timing of first ANC visit was high in Zambia compared to Nigeria. Previous studies in Nigeria have identified high prevalence of ANC attendance among women [30][31][32]. These studies reported higher prevalence of ANC visits, compared to what was found in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…This may be due to differences in access of health centers nearby and study area (rural). The finding was slightly low as compared to Nigeria (67%) [29], and this may be due to differences in socioeconomic and cultural factors. It was also slightly lower than a study conducted in Ambo town (84.9%) [21], and this may be due to study area difference (the study covers more rural areas).…”
mentioning
confidence: 55%